Design and analysis of urban car for Shell eco marathons Asia - Muhammad Firdaus, Othman (2012)
Shell Eco Marathon Asia is a competition based on car race, which requires the participant to design and fabricate the most fuel saving cars. There are two categories being promoted, which are prototype and urban car type. The team representative in this category known as the SAE - UMP Chapter is taking the challenge and builds up the urban car for the 2010 events at the Sepang International circuit, Malaysia. For that year, the team has won the third place in urban category. Since then, various improvements have been carried out by the team to compete for the top 3 position and create the most efficient car ever build in Universiti Malaysia Pahang. This thesis focuses on improvement of existing model in terms of aerodynamics. Aerodynamic is an important area of study as it relates to parasitic load experienced by the engine. The objective of this project is to design fives new model with the improved drag coefficients compared to existing models and finally to select the best design in terms of the aerodynamic features. The CFD analysis was performed by using Flow Simulation in Solidworks with standard condition where air density equal to 1.184 kg/m³ and at 1 atm environment pressure. The relative velocity of the analysis varies from 40 km/h to 90 km/h due to the minimum allowed velocity and maximum capable velocity of the car on track. The result of simulation shows that model 2 has the minimum drag coefficient which is equal to 0.281 and has improved the Cd by 37% compared to existing models. In this analysis, the most aerodynamic body is the one with minimum drag coefficient, minimum aerodynamic power and minimum relative pressure over the wake region. In selecting the model, the method of the Spider-web graph plot was used to visualize the widest area covered by the model in parameter axis. At the end of the analysis, model 2 shows the widest area covered in the graph plot which by quantitative measure, model 2 has the minimum drag coefficient, minimum aerodynamic power and minimum relative pressure over the wake region in the environment among the other 4 models.